What is an evidence-based appropriate workup? - Zimmern, Philippe E. (Canadian Urological Association Journal, 2012)
At the present time, there is no evidence-based guidance available for workup of stress urinary incontinence (SUI). In the absence of such evidence, we must rely on expert consensus, which dictates that a workup should typically include documentation of SUI, assessment of impact on the patient, and information on voiding function. Typical assessment may need to be adjusted for more complicated populations (e.g., those with mixed incontinence, those who have failed previous treatment).